Psychosocial Dimensions of Religious Founding - Hutch, Richard A (Journal of Dharma, 1984)
In her massive historical survey of notable American women, which spans the time from the colonial period up to and around 1920, editor Janet Wilson James has catalogued no fewer than thirty-eight women as "religious founders." I Not only does she include the most notable women founders like Mary Baker Eddv, who in 1866 slipped on some ice, was placed in bed, and then arose from her bed, as she put it later, "on the third day," and went on to found the Christian Science movement. James also gives places of prominence to lesser known figures like Ann Ayres, founder of the first monastic order for women of the Episcopal Church in America in 1852. Much of the field of women’s religious history still is unexplored. However, the biographies accumulated and catalogued by Janet James offer enough information about the activities and concerns of American women in the world of affairs to make possible an attempt at synthesis. At least, it is important to begin.